Proline Functionalized UiO-67 and UiO-68 Type Metal-Organic Frameworks Showing Reversed Diastereoselectivity in Aldol Addition Reactions - Kutzscher, Christel; Nickerl, Georg; Senkovska, Irena; Bon, Volodymyr; Kaskel, Stefan (Chemistry of Materials, 2016)
Functionalization of dicarboxylate linkers with proline was used to generate catalytically active metal-organic frameworks (MOFs) for diastereoselective aldol addition. Due to high robustness and chemical stability, zirconium based MOFs, namely UiO-67 and UiO-68, were chosen as catalyst hosts. During the MOF synthesis, utilizing Boc protected proline functionalized linkers H2bpdc-NHProBoc and H2tpdc-NHProBoc, in situ deprotection of the Boc groups without racemization is achieved, enabling direct application of the enantiopure, homochiral MOFs in catalytic reaction, without further postsynthetic treatment. Solvent screening and kinetic studies as well as cycling tests were used to evaluate the conditions for diastereoselective aldol addition using a model reaction of 4-nitrobenzaldehyde and cyclohexanone. High yields (up to 97%) were achieved in reasonable reaction time using ethanol as solvent. In comparison to homocatalytic reactions catalyzed by l-proline and its derivatives, MOFs showed opposite diastereoselectivity attributed to the catalytic sites in confined pore space rendering this class of materials as promising catalysts for fine chemicals production.
CRIS-Team Scopus Importer:2023-03-20